Evaluation of protective effects of melatonin on free radical metabolism in rat kidney during ischemia-reperfusion - Nisari, M.; Yay, A.; Ertekin, T.; Nisari, M.; Al, Ö.; Ceylan, D.; Önder, G. Ö.; Kavutcu, M. (Ukrainian Journal of Nephrology and Dialysis, 2019)
The purpose of this research was to investigate the possible protective effect of melatonin, as a potent antioxidant on I/R-induced renal injury in rats. Methods. We used 28 female Wistar albino rats weight 200-250g. The rats were randomly divided into 4 groups. Control Group (C): They were fed with only standard rat diet and tap water without drug injections or ischemia-reperfusion. Melatonin Group (M): 25 mg/kg melatonin was administered i.p 30 min. Ischemia/Reperfusion Group (I/R): Rats were subjected to 45 min of renal pedicle occlusion followed by 24 hours reperfusion. Melatonin+ischemia/reperfusion Group (M+I/R): Melatonin (25 mg/kg) was administered 30 min prior to ischemia and immediately before the reperfusion period. Rats were subjected to 45 min of renal pedicle occlusion followed by 24 hours reperfusion. Results. While MDA levels increased in the I/R group, SOD and GST activities were seen to be significantly increased. Although the increase of the SOD activity was observed in the M+I/R group, no meaningful difference was found. MDA levels were significantly decreased in M+I/R group compared to the control group, CAT and GST activities were significantly increased. Conclusions. Our results show that the treatment with M may prevent kidney damage due to ischemia result in increasing oxidant stress peroxidation damages further. Melatonin or its metabolites are capable of neutralizing free radicals and non-radical oxygen-based reactants. This study suggests that melatonin may be an effective antioxidant agent.